Modernism: Dehumaniztion of Art? - Jankauskas, Skirmantas (Problemos, 1986)
The art of the end of the 19th and of the beginning of the 20th centuries has undergone significant changes, so-called phenomenon of modernism. Spanish philosopher J. Ortega y Gasset has assessed those changes as the dehumanization of art. In the article an attempt is made to consider the modernism in the context of the general crisis of the culture of Western Europe. As the result the meaning of the paradoxical inference of Spanish philosopher is shown.